Application of the Thioacid‐Azide Ligation (TAL) for the Preparation of Glycosylated and Fluorescently Labeled Amino Acids. Issue 3 (27th March 2015) - Rohmer, Katja; Mannuthodikayil, Jamsad; Wittmann, Valentin
Abstract: The reaction of thiocarboxylic acids with azides (thioacid‐azide ligation, TAL) is a chemoselective transformation, leading to the formation of amide bonds. Especially in the case of electron‐deficient sulfonyl azides, the reaction occurs in excellent yields, within minutes at room temperature, in a broad range of solvents. In this article, the application of TAL for the synthesis of glycosylated and dansylated amino acids is reported. 2‐Azidosulfonylethyl glycosides were prepared from peracetylated monosaccharides and reacted with thioacid‐containing derivatives of aspartic acid and glutamic acid. Likewise, aromatic sulfonyl azides were employed. Ligation products were obtained in yields of up to 96 %. Different conditions for the generation of the thioacids were compared. Whereas reaction of succinimidyl esters with sodium hydrogen sulfide led to concomitant formation of diacyl disulfides, trityl thioesters turned out to be suitable precursors for the in situ preparation of thioacids by mild acidolysis. Abstract :